2015
DOI: 10.1111/bjh.13517
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of carfilzomib, lenalidomide, vorinostat, and dexamethasone in patients with relapsed and/or refractory multiple myeloma

Abstract: SummaryResearch has shown that proteasome inhibitors (e.g., carfilzomib), immunomodulatory agents (e.g., lenalidomide), histone deacetylase inhibitors (e.g., vorinostat) and corticosteroids (e.g., dexamethasone) have synergistic anti-multiple myeloma (MM) activity. This phase I dose-escalation study evaluated a regimen combining carfilzomib, lenalidomide, vorinostat and dexamethasone (QUAD) in patients with relapsed and/or refractory MM. Seventeen patients received carfilzomib (15, 20, or , lenalidomide 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…With the goal of translating our findings to the clinic, we focused on the pan-HDACi SAHA (vorinostat), an FDA-approved drug for the treatment of cutaneous T-cell lymphoma (20). SAHA, a hybrid polar compound (47) with a longer half-life, lower toxicity, and greater stability than earlier HDACi has demonstrated encouraging activity in patients with relapsed and/or refractory multiple myeloma in combination with novel (carfilzomib, lenalidomide) or conventional (dexamethasone) drugs (22,48,49). Molecular mechanisms underlying SAHA activity are diverse and not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…With the goal of translating our findings to the clinic, we focused on the pan-HDACi SAHA (vorinostat), an FDA-approved drug for the treatment of cutaneous T-cell lymphoma (20). SAHA, a hybrid polar compound (47) with a longer half-life, lower toxicity, and greater stability than earlier HDACi has demonstrated encouraging activity in patients with relapsed and/or refractory multiple myeloma in combination with novel (carfilzomib, lenalidomide) or conventional (dexamethasone) drugs (22,48,49). Molecular mechanisms underlying SAHA activity are diverse and not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, phase I clinical trials with CFZ began and the drug was successfully investigated in additional clinical trials [105,106]. This included phase III clinical trials where it was shown that CFZ was effective in patients with relapsed and BTZ-chemoresistant disease [202,203]. Owing to its more selective mechanisms of action, CFZ had fewer side effects as compared to BZT including less pronounced neuropathy.…”
Section: Carfilzomib: Second-in-class Proteasome Inhibitormentioning
confidence: 99%
“…Recently developed quadruplet regimens have also been evaluated for managing multiple myeloma [37][38][39][40][41]. However, there are limited data on their relative efficacy and safety compared with triplets and doublets.…”
Section: Compared With Doublets Triplets or Quadruplets May Better Omentioning
confidence: 99%